2012
DOI: 10.1016/j.envint.2012.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of DNA damage in humans inhabiting a volcanically active environment: A useful tool for biomonitoring

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. The present study was designed to evaluate whether chronic exposure to a volcanically active environment might r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 55 publications
(89 reference statements)
0
14
0
1
Order By: Relevance
“…A study from Furnas, Azores showed evidence of DNA damage in residents of volcanic active areas in comparison with an area without manifestations of volcanic activity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study from Furnas, Azores showed evidence of DNA damage in residents of volcanic active areas in comparison with an area without manifestations of volcanic activity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, toxic heavy metals are also released and deposited in the airways and hair and can be retained in tissues, increasing the inflammatory, oxidative stress, DNA damage response and, ultimately, the carcinogenic response [10,12,30].…”
Section: Impact On Morbiditymentioning
confidence: 99%
“…A recent study indicated an association between chronic exposure to volcanically active environments and the occurrence of DNA damage in human buccal epithelial cells, revealing that noneruptive active volcanism is a risk factor of carcinogenesis [11]. In a further study, when mice have been exposed to volcanogenic air pollution, alveolar space, alveolar perimeter, and lung structural functionality ratio decreased, while their alveolar septal thickness increased [12].…”
Section: Introductionmentioning
confidence: 96%